Aligned MHD mixed convection flow of hybrid nanofluid over a vertical plate with convective boundary condition / Azwani Ahmad Rusjati - Ahmad Rusjati, Azwani (2021)
The present study investigate the behavior of aligned MHD mixed convection flow of hybrid nanofluid passing through the vertical plate with convective boundary conditions. In this study, it was assumed that the hot fluid was connected on the left surface of the plate, while the cold fluid connected on the right surface of plate. The analysis on the behaviour of hybrid nanofluid and nanofluid towards five different parameters which were magnetic field inclination angle, magnetic interaction, nanoparticles volume fraction, mixed convective parameter and Biot number had been done with Ag-CuO/water and CuO/water represent hybrid nanofluid and nanofluid, respectively. The governing partial differential equations together with its boundary conditions are reduced to a system of the non-linear ordinary differential equation by using similarity transformation. Then, the reduced equations and corresponding boundary conditions are solved numerically using fourth-order Runge-Kutta Method. In order to show the reliability of the numerical procedure, a comparison on the results for skin friction and Nusselt number with existing literature has been done and excellent agreement is obtained. The effect of thermophysical parameters on fluid velocity, temperature, skin friction and Nusselt number are discussed. As a result, the heat transfer of Ag-CuO/water hybrid nanofluid is higher than the CuO/water nanofluid. Ag-CuO/water hybrid nanofluid also dominated the velocity and temperature profile in all thermophysical parameters. The skin friction coefficient and Nusselt number increase with an increase in the inclination angle of magnetic field, magnetic field parameter, volume fraction of nanoparticles, mixed convective parameter and Biot number for both Ag-CuO/water hybrid nanofluid and CuO/water nanofluid.